Acceptability and feasibility of integration of HIV care services into antenatal clinics in rural Kenya: A qualitative provider interview study - Winestone, Lena E. (2011)
The aim of this study was to explore the perspectives of healthcare providers on the advantages and disadvantages of integrating HIV care services, including highly active antiretroviral therapy (HAART), into antenatal care (ANC) clinics in rural Kenya. We conducted a qualitative study using in-depth interviews and thematic analysis; 36 healthcare providers from 6 health centres in Nyanza Province, Kenya participated. Effects on service providers included increased workload due to the incorporation of specialised HIV services into ANC clinics. Providers observed that integration results in decreased patient time spent at the health facility, increased efficiency, and closer provider-patient relationships; all leading to increased patient satisfaction. Providers also said that women would be more likely to receive HAART and adhere to their treatment as a result of improved confidentiality and decreased stigma. However, a minority of providers noted that integration could result in longer appointment times for HIV-positive women at ANC clinics leading to inadvertent disclosure. Integration could lead to strengthened antenatal care, postpartum care, prevention of mother-to-child transmission and HIV care for women and their families. However, integration efforts need to take into account potential negative effects on ANC provider workload, disclosure, and the quality of care.